PELAKSANAAN HAK KONSTITUSIONAL WARGA NEGARA DALAM AKSI BERDEMONSTRASI DI KOTA PEKANBARU : Pelaksanaan Hak Konstitusional Warga Negara Dalam Aksi Berdemonstrasi - Andrizal, Andrizal; Yandra, Alexsander (Mendapo: Journal of Administrative Law, 2023)
Demonstrating is a form of expressing opinions in public that is guaranteed by the constitution, this is very important because it is part of human rights, but in practice it must pay attention to the principle of balance between rights and obligations, respecting the rights of others, not anarchy, using language that polite and ethical as regulated by existing regulations, but in practice in the city of Pekanbaru it is not uncommon for demonstrators to do the opposite. The research method, this type of research is sociological legal research. research by obtaining data directly into the field in the form of interviews. The research location was carried out in Pekanbaru City. The reason for determining the location in Pekanbaru City is the location with the most occurrences and the target location for demonstrations in Riau Province compared to other Regencies/Cities in Riau Province. The results of this study concluded that the implementation of citizens' constitutional rights in demonstrating in the city of Pekanbaru has not been effective. because demonstrations tend not to inform the police about their action plans, beyond the time limit set by existing regulations, the actions turn out to be disorderly and tend to be anarchic. Obstacles in carrying out demonstrations include time limits, failure to follow action plan reporting rules, irresponsible repressive security, intervention from the security forces, provocations, officials or targets for action disappearing, misunderstandings between demonstrators and security forces resulting in physical conflict, destruction/confiscation /deprivation of action props. Efforts that must be made include: outreach or legal counseling on the Freedom of Expressing Opinions in Public to elements or components of society who have the potential to carry out demonstrations.